Opinions citizens to the drug policy in six cities of latin america (2014)
The aim of the paper is to explore opinions and attitudes of citizens in six Latin American cities from drugs- consumption and production-and drug policies. This paper asks how liberals are the opinions of citizens about drugs and drug policy, if any difference to this issue among the various Latin American cities, and what is the relationship between socio-demographic and contextual factors with ideological these opinions and attitudes. The data indicate that these opinions are based on their ideological position, how liberal are moral attitudes, characteristics of the social environment with respect to the levels of drug use and unsafe levels of their neighborhoods.